Metabolomics and Lipidomics Reveal the Effect of Hepatic Vps33b Deficiency on Bile Acids and Lipids Metabolism - Fu, Kaili; Wang, Conghui; Gao, Yue; Fan, Shicheng; Zhang, Huizhen; Sun, Jiahong; Jiang, Yiming; Liu, Conghui; Guan, Lihuan; Liu, Junling; Huang, Min; Bi, Huichang (Frontiers in Pharmacology, 2019)
Vascular protein sorting-associated protein 33B (VPS33B) plays important roles in hepatic polarity, which directly maintains the functional structure of the liver. It has reported that VPS33B has close association with arthrogryposis, renal dysfunction and cholestasis (ARC) syndrome. Unfortunately, no further studies were conducted to reveal the role of Vps33b in the homeostasis of bile acids. In the current study, hepatic Vps33b-depleted male mice were used to investigate the metabolomics and lipidomics profiles of hepatic Vps33b deficiency based on ultrahigh-performance liquid chromatography coupled with an electrospray ionization high-resolution mass spectrometry (UHPLC-ESI-HRMS) system. Hepatic Vps33b-depleted male mice displayed cholestasis and slight liver damage with increased serum levels of ALT, AST, ALP and T-Bili compared to wild-type mice. Targeted metabolomics analysis of bile acids revealed that increased taurine-conjugated bile acids accumulated in the serum of hepatic Vps33b-depleted mice, while unconjugated bile acids were prone to decrease, accompanied by the regulation of bile acid homeostasis-related genes. In addition, lipid profiles were significantly altered with the lack of Vps33b in the liver. A variety of lipids, such as triglycerides and sphingomyelins, were significantly decreased in the liver and increased in the serum of hepatic Vps33b-depleted mice compared to those in wild-type mice. Our study demonstrated that Vps33b influences the progress of liver metabolism both in bile acid circulation and lipid metabolism, which is involved in the progression of liver cholestasis in mice.